(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Several prospective tidal energy sites have been identified around the UK, however, little is known about the specific, and often complicated, hydrodynamics in many of these area [1]. Many sites comprise complicated seabed and coastline configurations, which can not only give rise to fast-flowing currents, but also results in highly turbulent and spatially-varying currents. These latter features are undesirable characteristics for devices. Tidal stream energy developers seldom design devices to suit a particular site, rather devices are designed and suitable sites located subsequently. This reduces the number of viable sites as each device has its own design constraints, e.g. minimum water depth, minimum velocity, etc. In order to maximise the exploitability of these sites, where space is generally limited, it would be more beneficial for developers to design devices once site conditions/constraints are better understood. An open-source tool is being developed that determines the physical constraints of a site based primarily on bathymetry and current velocities (measured and/or modelled). This tool aims to optimise a site to help developers understand what conditions need to be met in order to maximise energy generation – it will also identify which areas are unsuitable depending on the device design. The flexibility of the tool ensures two key aspects: • For existing devices, the device design parameters can be selected to show which areas are viable that meet these parameters (e.g. maximum bed slope, maximum current velocity, etc.); • For devices yet to be designed, different design parameters can be selected to optimise a site to help maximise the energy that can be extracted from a particular site. The tool is being written in Python with a QGIS front end to allow the user to make changes readily and choose which parameters are important. Not only will the tool identify suitable sites based on user-defined parameters, it will also calculate how much power is available (in kW/m2) based on velocity data. Given the data availability and interest from tidal energy developers in Ramsey Sound (Figure 1) and to the west of Ramsey Island in West Wales, UK, this site has been chosen as a case study. This site also experiences significant spatial and temporal variation in flow, caused in part by a narrowing of the Sound, which accelerates flow [2]. Once this tool has been proven it will be expanded to assess the viability of other tidal energy sites, both in the UK and overseas. Sensitivity testing is currently underway to determine how sensitive the tool is to data resolution. For example, do higher resolution bathymetry and velocity datasets provide a marked difference in the areas that are viable. This tool will demonstrate that developers (and other relevant parties in the supply chain) cannot rely on first-order appraisals, which may make energetic tidal straits attractive sites for development since their resource potential depends on flow conditions that are fundamentally local.